Analysis of The Effectiveness of Web Portals used in Academic Institutions of Tribhuvan University - Pandey, Romkant; Diyal, Suresh Bahadur; Malla, Vijaya (Innovative Research Journal, 2023)
For many academic institutions, the website has been used as a tool for inter- and intra-organizational information exchange. Since universities and colleges have started to use their websites as information centers, effective website design and functionality are very important for higher education institutions to attract students and share information regarding academic activities. The researcher observed various web portals based on the technology used, user perspective, and compatibility of some academic institutions observing that many students spent a lot of time on the Internet than in libraries. A checklist is formed to collect data from the websites and explains it in different tables and figures. Thus, the study is designed to provide insights into ICT colleges' websites' effectiveness.All the websites are based on PHP, mostly WordPress, The use of Bootstrap is quite good, comparatively websites have slow page loading speeds due to the lack of code and image optimization though valid and standardized codes were used. The use of media queries was very impressive but the lack of proper placing of CSS codes made it visually poor on some of the devices. This research explores the effectiveness of portals and websites in academic institutions and some recommendations are made based on the findings.